The Effect of Job Satisfaction on Organizational Commitment: a Study of Employee’s Performance in Malaysian Call Centers - Zandi, Gholam Reza; Aslam, Ayesha; Nasir, Muhammad Umar; Jiayi, Dong (International Journal of Engineering and Technology, 2018)
The purpose of this research paper is to sort out the relationship between employee’s performance and organizational commitment and job satisfaction in the call centers of Malaysia. Foremost research objective is to find out the reasons and factors that may influence the employee’s performance, dimensions for research are Affective Commitment, Continuance Commitment, Normative Commitment, Extrinsic Job Satisfaction, Intrinsic Job Satisfaction on employees performance. Data has been collected from approximately 100 employees who are currently working in call centers of different companies of telecom sector of Malaysia. On SPSS, all statistical analysis applied to analyze the association and cause and effect relationship. As a conclusion, researcher comes up with the findings that there is a significant relationship between job satisfaction and organizational commitment along dimensions with employee’s performance. The most influential factor on employee’s performance is extrinsic job satisfaction, which has more influence on performance of employees as compare to the other factors.